2015
DOI: 10.1007/s11274-015-1888-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting potential of endophytic fungi isolated from Solanum nigrum leaves

Abstract: Fungal endophytes have been characterized as producers of phytohormones and potent promoters of plant growth. In this study, two fungal endophytes, Fusarium tricinctum RSF-4L and Alternaria alternata RSF-6L, were isolated from the leaves of Solanum nigrum. Culture filtrates (CFs) from each isolate were initially screened for indole compounds, and assayed for their ability to promote the growth of Dongjin rice plants. Nearly all plant growth attributes examined (i.e., chlorophyll content, root-shoot length, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 19 publications
6
52
0
4
Order By: Relevance
“…The endophytic fungi of Potentilla fulgensis is reported to have the metabolic machinery to secrete plant growth hormones such as cytokinins, auxins and gibberellins which promote seed germination and growth (Bhagobaty & Joshi 2009). Khan et al (2015) reported that two fungal endophytes, Fusarium and Alternaria isolated from the leaves of Solanumnigrum, increased the chlorophyll content, root-shoot length, and biomass production of Dongjin rice plantswhen inoculated at the seedling stage. Gas chromatography/ mass spectrometry analysis for the culture filtrates of each fungal endophytic isolate revealed that both Fusarium and Alternaria could produce 54 and 30 µ.gm.L -1 of indole acetic acid, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The endophytic fungi of Potentilla fulgensis is reported to have the metabolic machinery to secrete plant growth hormones such as cytokinins, auxins and gibberellins which promote seed germination and growth (Bhagobaty & Joshi 2009). Khan et al (2015) reported that two fungal endophytes, Fusarium and Alternaria isolated from the leaves of Solanumnigrum, increased the chlorophyll content, root-shoot length, and biomass production of Dongjin rice plantswhen inoculated at the seedling stage. Gas chromatography/ mass spectrometry analysis for the culture filtrates of each fungal endophytic isolate revealed that both Fusarium and Alternaria could produce 54 and 30 µ.gm.L -1 of indole acetic acid, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A pestalotin analogue isolated from the Pestalotiopsis microspora exhibited significant gibberellin activity against Distylium chinense seeds and increase germination rate (85.56%) . The Fusarium tricinctum and A. alternata derivatives of indole acetic acid enhanced the plant growth (Khan et al 2015).…”
Section: Plant Growth Stimulantsmentioning
confidence: 97%
“…However, the exploration of endophytic fungi as biocontrol agents against this disease is rarely considered (Kavroulakis et al, 2007). Interestingly, some wild Solanum species have been explored as potential sources of bioactive molecules and biocontrol agents (Khan et al, 2015;Aydi Ben Abdallah et al, 2016). In the present study, a collection of fungal isolates naturally associated with S. linnaeanum was screened for its ability to suppress FCRR and to promote tomato growth when applied as conidial suspensions or cell-free culture filtrates.…”
Section: Discussionmentioning
confidence: 99%